Bentuk-bentuk Campur Kode dan Alih Kode Pada Halaman Facebook Kementerian Kesehatan RI (Kajian Sosiolinguistik) - Mahes Solekhudin; Hany Nisa; Robert Rizki Yono (Peneliti.net, 2022)
This study aims to identify and describe the forms of code mixing and code switching on the Facebook page of the Indonesian Ministry of Health. In reviewing this research, researchers used qualitative methods as research procedures that produced descriptive data. In collecting data, the writer uses documentation technique. After collecting the data from the results of the documentation, then it is described by providing analyzes and then the final conclusion is given. The results showed that from 9 code mixing data and 4 code switching data, English was more often used in code mixing and code switching than other languages.